Comprehensive In Silico Analysis of Christinin Molecular Behaviour from Ziziphus spina-christi Leaves on Propionibacterium acnes - Darusman, Fitrianti; Fakih, Taufik Muhammad (Pharmaceutical Sciences and Research, 2021)
The role of in silico studies in the discovery of new drugs is very important and interesting in the recent years, where the results can be used as confirmation of the results of in vitro tests carried out experimentally in the laboratory. One of the herbal ingredients is Ziziphus spina-christi leaves with effective antibacterial activity, such as for acne-causing bacteria, namely Propionibacterium acnes. This is because it contains main secondary metabolites with saponins as the major components which contain christinin as its active compound. There are four known types of christinin, namely christinin-A, christinin-B, christinin-C, and christinin-D. In this study, the molecular interaction of the christinin compound was tested to predict its affinity for Propionibacterium acnes compared to clindamycin, as well as to determine the level of safety on the skin so that it can be applied as a topical anti-acne dosage form. In silico studies, including molecular docking and toxicity prediction, were used to assess the activity of four molecules of the christinin compound on c-Jun N-terminal kinase (JNK) macromolecules. The christinin molecules form a strong and stable molecular interaction with the active site of the binding of c-Jun N-terminal kinase (JNK) macromolecules. Interestingly, the christinin compound molecules also has a fairly good level of safety based on the three identified parameters. Based on this results christinin compound molecules has potential to be developed as c-Jun N-terminal kinase (JNK) inhibitors candidate to control of skin infections caused by Propionibacterium acnes which has potential as a topical anti-acne.